Vascular Flora and Endemism of Ormanüstü Planning Unit (Maçka-Trabzon), Turkey - Uzun, Alper; Terzi̇oğlu, Salih (Kastamonu University, 2021)
Abstract
Aim of study: Aim was to determine the vascular flora of the Ormanüstü Planning Unit (Karadeniz Technical University Education-Research and Application Forest).
Area of study: The research area is under the influence of the Euro-Siberian phytogeographical region and is represented with a high rate (44%, 288 taxa). Irano-Turanian and Mediterranean elements are represented by 26 (4%) and 22 taxa (3%), respectively. Totally 320 taxa (49%) are multi-regional or of unknown origin. In addition, 33 endemic (5%), 12 rare (1.8%), 5 alien (0.8%) and 17 cosmopolitan (2.6%) taxa were identified.
Material and methods: The entire study area was visited periodically and plant samples were collected from 166 sample plots (1000 m2), and then they were pressed with wooden frames. Approximately 1800 vascular plant specimens were collected between the years 2005 and 2008 to form the floristic list.
Main results: Studies revealed the presence of 656 taxa (585 species, 62 subspecies and 9 varieties) belonging to 95 families and 354 genera. Of these, 22 taxa (3.4%) are ferns and 634 (96.6%) are seed plants. The best-represented families are as follows; Asteraceae (75), Poaceae (48) and Fabaceae (41). According to richest genera; Campanula (14), Carex (10), Alchemilla (9) and Geranium (9) have the greatest number of taxa.
Highlights: It was concluded that the study area is important in terms of plant diversity. The discovery of a new species from this area, described by us and published in 2009 (Astragalus ansinii Uzun, Terzioğlu & Pal.-Uzun), supports this fact.
Keywords:
Keywords: Vascular flora; Endemism; Colchis; Maçka; Turkey; Vasküler flora; Endemizm; Kolşik; Maçka; Türkiye; 2. Zero hunger; 4. Education; 15. Life on land